SOLUTION OF OPEN TRANSPORTATION PROBLEMS - S. V. Petrunin; G. V. Kreneva (Научный вестник МГТУ ГА, 2016)
The article examines open transportation problems proposing to apply a modernized PC-method for their solution. Some of transportation problems could be reduced to those with bounded-variables solution for which is also given by the authors.